From Mitropa Cup to UEFA Cup: the role of UEFA in the establishment of a European scale in football, 1927–1972. (17th November 2019) - Vonnard, Philippe
ABSTRACT: Since the 1920s, many European exchanges began to exist in the domain of football. However, it was during the 1950s that a European scale was established primarily due to the creation of UEFA (Union of European Football Associations) in 1954, which quickly organized the first European tournament in the game's history– The European Champions Clubs' Cup. The present essay argues that Europeanization of the game has to be understood in a long-term perspective. The papers examines the creation and development of three competitions as key defining events, which represented different stages of the Europeanization of the game: Mitropa Cup (created in 1927), European Champion Clubs' Cup (created in 1955) and UEFA Cup (created in 1971). Thus, afocus on these cases can help us better understand the background of the Europeanization of the game which happened during the 1990s.